Síntese e caracterização de zeólita LTA impregnada em óxido de grafite para adsorção de prata em leito fixo e condições pressurizadas - Reske, Gabriel Diogo (2024)
This study presents an investigation detailing the methodology and characterization of a novel material synthesized via the impregnation of zeolite LTA with graphite oxide (GOIZ) for the purpose of Ag (I) adsorption. The first part of the research focused on batch adsorption experiments, where the new adsorbent was characterized and compared with its precursor materials, demonstrating superior performance in Ag (I) adsorption. The adsorption followed the Pseudo-second-order kinetic model and the Freundlich isothermal model with an endothermic nature. The new material presented a remarkable Ag (I) uptake, reaching 142.06 mg/g at 55 °C. These results highlight the considerable potential of graphite oxide impregnated with zeolite LTA as an effective adsorbent for Ag (I) removal from aqueous streams. Furthermore, the Ag (I)-loaded adsorbent exhibited notable antimicrobial activity, with inhibition zones in the growth of Staphylococcus aureus and Escherichia coli of 8 mm and 9 mm, respectively. The study also explored the potential of GOIZ in continuous Ag (I) removal under elevated temperature and pressure conditions using a fixed bed column. The adsorption performance of GOIZ was significantly enhanced at elevated temperatures and pressures, with better results achieved at 200 °C and 25 MPa. Under these conditions, the maximum stoichiometric capacity of the column was 407 mg/g, compared to 47 mg/g at 25 °C and 0.1 MPa. Mathematical modeling using Dose-response models accurately predicted Ag (I) adsorption behavior in the fixed bed column packed with GOIZ, even under extreme temperature and pressure conditions, demonstrating the model's suitability for describing experimental curves. Furthermore, the study delved into the interaction mechanism between Ag (I) and GOIZ, uncovering a dual process governed by the oxidation-reduction mechanism and electrostatic interactions.